The Guidelines for Developing Teamwork Competency of Teachers in Digital Era under The Secondary Educational Service Area Office Nonthaburi - Ngampiem, Hemsuda; Suwansumrit, Chalabhorn (Journal of Graduate MCU KhonKaen Campus, 2026)
The objectives of this research were 1) to study the teamwork competency of teachers in digital era under The Secondary Educational Service Area Office Nonthaburi 2) to compare the opinions of teamwork competency of teachers in digital era, classified by age, education level, work experience and school size, and 3) to study guidelines for the teamwork development competency of teachers in digital era under The Secondary Educational Service Area Office Nonthaburi. The study samples consisted of 5 school administrators, 320 teachers. The research instruments were an interviews and questionnaire with a content validity, IOC values, between .67–1.00 and a reliability value of .98. The data analysis employed using frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, LSD, and content analysis. The research results were as follow: 1) The teamwork competency of teachers in digital era was at a high level in overall, ranking from the highest to the lowest mean: role of leader and followers, adapting with various situation, participation with others for developing education, support with colleague, and encouragement to colleague; 2) the opinions the teachers on teamwork competency of statistically teachers in digital era, classified by age, work experience and school size were not different in overall, while the differential education level had statistically significant differences at the level of .05, and 3) the suggested guidelines: for school administrators to improve the teamwork competency included that; they should active support, reinforcement and mutual trust they should promote activities to develop relationships and informal learning exchange platforms, they should developed to increase team strength and achieve sustainable educational goals.